Que impactos esperar da participação na elaboração de políticas públicas? Proposta de um conjunto de critérios para avaliar o processo participativo do Plano Diretor de São Paulo - Araujo, Theo Lovizio de (2016)
Many positive results are normally assigned to participation, ranging from the improvement of public policies to the democratization of the State and the promotion of a culture of participation in public affairs. In Brazil, participatory arrangements were broadly institutionalized in the past decades and are now a part or the legal framework that structures public administration. Very little was done, however, to establish standards to verify the efficacy of these arrangements. This work studies the participatory process for the elaboration of the Master Plan of the city of São Paulo ('Plano Diretor Estratégico'), held between March and September 2013 by the city’s Urban Development Secretary ('Secretaria Municipal de Desenvolvimento Urbano'). With the aim of suggesting a set of criteria for the evaluation of this and of other participatory processes, this study deepens its regard over the spaces of interaction between government and society during the elaboration of the Plan. Through the analysis of documents and qualitative research based on interviews with key participants and public administrators, it identifies and applies a set of evaluation criteria to the participatory process of the Master Plan. By doing this, it also reveals a double logic behind the relationship between State and society during the process. On the one hand, it comprised broad channels for participation and innovative efforts by the local authorities to put forward a methodology based on dialogue and consent. On the other hand, it was characterized by an active role of the State in managing the conflicts between a restricted number of organized sectors, such as the housing movement, the housing market and neighbor associations from Strictly Residential Areas ('Zonas Estritamente Residenciais'), in a relationship typical of corporativism.